From unemployment benefits to unemployment accounts - Jonathan Michael Orszag; Dennis J. Snower (Institute for the Study of Labor (IZA), 2002)
We explore the implications of replacing current unemployment benefit (UB) systems by unemployment accounts (UA). Under the UA system, employed people would be required to make ongoing contributions to their unemployment accounts, and the balances in these accounts would then be available to them during periods of unemployment. The government would be able to undertake balanced-budget redistributions among the UAs, taxing the contributions of the rich and subsidizing those of the poor. When people retire, they could use their remaining UA balances to top up their pensions. Under the unemployment benefit system, people are in effect rewarded for being unemployed (through the unemployment benefits) and penalized for being employed (through the taxes that finance the unemployment benefits). The UA system alleviates these externality problems. For when an unemployed person makes withdrawals from his UA, he is thereby diminishing the amount of funds that are available to him later on.
Keywords: J65; J23; J68; J32; J38; J64; 330; unemployment accounts; redistribution; employment; unemployment; pensions; unemployment benefits; Arbeitslosenversicherung; Reform; Vermögensbildung; Arbeitsangebot; Ökonomischer Anreiz; Theorie